Getting started with time series forecasting in Python. (Manning Publications, 2022)
Introductory lesson on time series forecasting in Python. Marco Peixeiro explores the random walk model, MA(q) and AR(p) models. Throughout the lesson, he explores the foundational concept of stationarity, and learn how to use the ACF and PACF plots for forecasting.